A Schematic Representation of the Professional Identity Formation and Socialization of Medical Students and Residents. (June 2015) - Cruess, Richard L.; Cruess, Sylvia R.; Boudreau, J. Donald; Snell, Linda; Steinert, Yvonne
<x xml:space="preserve">Abstract</x> Recent calls to focus on identity formation in medicine propose that educators establish as a goal of medical education the support and guidance of students and residents as they develop their professional identity. Those entering medical school arrive with a personal identity formed since birth. As they proceed through the educational continuum, they successively develop the identity of a medical student, a resident, and a physician. Each individual's journey from layperson to skilled professional is unique and is affected by "who they are" at the beginning and "who they wish to become." Identity formation is a dynamic process achieved through socialization; it results in individuals joining the medical community of practice. Multiple factors within and outside of the educational system affect the formation of an individual's professional identity. Each learner reacts to different factors in her or his own fashion, with the anticipated outcome being the emergence of a professional identity. However, the inherent logic in the related processes of professional identity formation and socialization may be obscured by their complexity and the large number of factors involved. Drawing on the identity formation and socialization literature, as well as experience gained in teaching professionalism, the authors developed schematic representations of these processes. They adapted them to the medical context to guide educators as they initiate educational interventions, which aim to explicitly support professional identity formation and the ultimate goal of medical education—to ensure that medical students and residents come to "think, act, and feel like a physician."